Attachment parenting : developing connections and healing children - Becker-Weidman, Arthur, 1953-; Shell, Deborah, 1952- (Jason Aronson, 2010)
"Attachment Parenting describes a comprehensive approach to parenting children who have a history of neglect, abuse, orphanage care, or other experiences that may interfere with the normal development of attachment between parent and child. Grounded in attachment theory, Attachment Parenting gives parents, therapists, educators, and child-welfare and residential-treatment professionals the tools and skills necessary to help these children"--EBL